Pengaruh Kualitas Layanan Front Office terhadap Minat untuk Berkunjung di DPMPTSP Kota Depok - Indri Hermawaty Noorsamsu; Sri Hermawati (MES Bogor, 2023)
The purpose was to determine the effect of service quality on return visit interest through community satisfaction. This research method quantitative survey type. The object is service quality on public satisfaction and interest in visiting again. The research subjects were people who conducted SIUP licensing at the front office of the One- Stop Investment and Integrated Services Office (DPMPTSP) located in Depok City. The sampling technique random sampling. The sample amounted to 120 respondents. The results showed that service quality had a significant effect on community satisfaction and interest in visiting again. Public satisfaction has a significant effect on interest in visiting again. All three variables have a significant value <0.05, which means H0 is rejected and Ha is accepted.